Feasibility of ratooning in Hevea : Early growth performance - Madhavan Jayashree; Abraham S T; Nair R B; Pothern Jacob; Varghese Y A (Proceedings of the 15th Plantation Crops Symposium, PLACROSYM XV, 10-13 December 2002, Mysore .pp.95-101.)
An experiment was carried out to study the feasibility of ratooniing as a propagation method in Hevea brasiliensis. Sprouting and subsequent growth of the ratoon plants in the first year were compared with conventionally bud grafted plants of the same clone and age grown in polybags. As expected, the sprouting percentage was lower (74.7;) in the tree stumps compared to that in the polubags (88.9;). On the other hand, the growth of the ratoons was superior to that of the poly bagged counterparts at the end of the first year, with significantly higher values for girth, height, number of whorld produced and retained, leaf size and weight, and specific leaf weight.
Keywords: Early growth performance; Hevea; Ratooning